PENINGKATAN KETERAMPILAN PROSES SAINS PESERTA DIDIK SMP MENGGUNAKAN MODEL PEMBELAJARAN GUIDED INQUIRY PADA MATERI KALOR - Lisda Rosanti; Elok Sudibyo (Jurusan IPA, Fakultas Matematika dan Ilmu Pengetahuan Alam, Universitas Negeri Surabaya, 2022)
This study aimed to describe the improvement of students' science process skills by implementing guided inquiry-based learning. The method in this study was pre-experiment with one group pretest posttest design. The subject in this study were 17 students of VII A class in SMP Negeri 2 Taman. The result of this study showed that the implementation of the guided inquiry-based learning was in the very good category, the N-Gain score obtained through the pretest and posttest of science process skills was in the high category, and the implementation of the guided inquiry-based learning obtained responses from students with a very good category. Based on the results, it can be concluded that the guided inquiry-based learning implementation can improve students' science process skills on heat.